2010
DOI: 10.1007/bf03404354
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Celebrity Death on Children’s Injury-related Emergency Room Visits

Abstract: he mass media may have both positive and negative effects on health and health care delivery. Health education campaigns delivered by the media influence the health of the population either by increasing knowledge, changing behaviour, or both. 1 In other contexts, the media in general and TV in particular have been shown to affect the psychological and physical wellbeing of children, especially with respect to obesity. 2,3 Media reporting of celebrities' health issues may also affect the public, but not always… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 17 publications
0
8
0
1
Order By: Relevance
“…Only age-group and sex of the uninjured controls could be assessed for accuracy and our observations were found to be valid. There was potential for misclassification of severe injury because factors other than severity could predict presentation to the ED, such as parental fear or anxiety influenced by a recent celebrity skiing death 39. It was unknown if non-consenting injured snowboarders presented to a non-study ED and were incorrectly classified as a minor injury.…”
Section: Discussionmentioning
confidence: 99%
“…Only age-group and sex of the uninjured controls could be assessed for accuracy and our observations were found to be valid. There was potential for misclassification of severe injury because factors other than severity could predict presentation to the ED, such as parental fear or anxiety influenced by a recent celebrity skiing death 39. It was unknown if non-consenting injured snowboarders presented to a non-study ED and were incorrectly classified as a minor injury.…”
Section: Discussionmentioning
confidence: 99%
“…26 There is at least one study available which showed a 60% increase in the pediatric injury visits to the emergency room during the week following the death of Natasha Richardson in Canada. 53 Also, 15% of neurosurgeons in various European countries bought a ski helmet after the German politician's slope incident mentioned earlier. 26 …”
Section: Study Limitationsmentioning
confidence: 99%
“…Google News found > 1,100 mentions of Natasha Richardson's death in international press just in the two months following the event. 53 It is possible that this coverage generated anxiety and subsequently modified treatment-seeking and other subjective behaviors. 26 There is at least one study available which showed a 60% increase in the pediatric injury visits to the emergency room during the week following the death of Natasha Richardson in Canada.…”
Section: Study Limitationsmentioning
confidence: 99%
“…In the winter season 2008/2009, a broad public discussion about ski helmet use has arisen after few fatal skiing injuries involving celebrities in Europe and North America (Jung et al., ; Keays & Pless, ; Ruedl et al., ). As a consequence of these public discussions, mainly based on fatalities of unhelmeted adult skiers, helmet use has become mandatory for children under 16 years in most Austrian provinces (Jung et al., ; Ruedl et al., ).…”
mentioning
confidence: 99%